Catatan Penelitian: Persepsi nelayan terhadap kebijakan subsidi perikanan dan konservasi di Kabupaten Aceh Besar, Provinsi Aceh - Zainal A. Muchlisin; Nur Fadli; Arifsyah M. Nasution; Rika Astuti (Depik, 2013)
Abstract. The objective of the present study was to collect information of fishermen perceptions  in Aceh Besar district. The study was conducted from June to August 2012, while the field survey conducted on 21 to 28 June 2012 at some fishing villages in Aceh Besar district namely: (a) Baitussalam and Mesjid, (b) Peukan Bada, (c) Leupung, Lhoknga and Lhoong, (d) Pulo Aceh, (e) Seulimum. The Results showed that most of  respondents were  in the productive age (31-45 years).  The majority of the respondents have recieved subsidies from a variety of sources both government and non-governmental organizations. The common type of subsidy were in the form of goods (in kinds) namely: boats, fishing gear and boat engines, and small portion in cash. In addition, the majority of fishermen stated that the type of assistance provided was in accordance with their needs as fishermen and most fishermen are still expected that fisheries subsidies should be continued. In regard to environmental  and conservation issues that  most fishermen agreed with the conservation area in the district of Aceh Besar. However, most of the respondents stated that they have not been involved in conservation activities. The fishermen need training in fishing technology, post harvest and conservation.Keywords: Habitat degradation, fish, skills and capital